Targets detection Analysis in the Passive Coherent Location System in Single Frequency Network - Juryca, Karel; Pidanič, Jan; Němec, Zdeněk (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The paper deals with the primary analysis of the target detection in the Passive Coherent Location system that exploits DVB-T transmitters in a Single Frequency Network. The analysis is based on the behavior of a Cross Ambiguity function and is done for one/more targets in one bistatic radar. The Single Frequency Network system uses the same central carrier frequency for all transmitters. The analysis shows that multipath effect significantly influences the determination of the precise accuracy of the maximum of the CA function.
Analýza detekce cílů v systémech pasivní koherentní lokace v jedno frekvenčních sítích
Keywords: Passive Coherent Location System